Kazakhstan's connectivity paradigms with China and India: a comparative analysis (Journal of Oriental Studies, 2021)
The world is undergoing irreversible structural changes in global geopolitical space. The dynamic development of Asian countries has brought significant changes to the geopolitical and geoeconomic structure of the world. The COVID-19 pandemic restrictions more than ever demonstrated the role of rising Asian states not only in providing manufacturing facilities but also in maintaining the global supply chain and logistics. The role of China in this process is significant. India also working on enhancing its connectivity channels, whilst the post-COVID global supply chain reality provides new opportunities for India’s aspirations. For Kazakhstan, which integrated with China’s Belt and Road Initiative, and working to connect to India’s alternative Chabahar port, the role of connectivity is critical. Given the geographic location that bridges Europe with Asia and provides alternative roads bypassing Russia, Kazakhstan's transit potential is immense.Against this backdrop, the paper reveals Kazakhstan’s state-of-the-art in transport sector in regard to China and India. First, we analyse the theoretical framework of China’s Belt and Road Initiative. Then, we explore China’s engagement with Kazakhstan, especially during the COVID-19 hindrances. We further provide India’s alternative connectivity visions from a comparative perspective. We conclude with the assessment of the current partnerships and opportunities to expand connectivity with Kazakhstan.The major argument of discussion is that although Kazakhstan has been widely integrating into China’s BRI, it still has successfully diversified its connectivity networks in line with its multivector policy.Keywords: China, India, Kazakhstan, connectivity, Belt and Road Initiative